Transform your communication with storytelling (Assemble You, 2023)
Andreas Loizou is a trainer and author who comes with a spectacular bio. A Leader in Residence at the University of Leeds, he's a published author and Business Writing guru. A qualified accountant, he won the Best Speaker at the internationally-renowned Financial Times Intro to the City Programme for six years running, has worked with Pearson Education, BNP Paribas, and countless other large organizations, and we're delighted to welcome him to The Power Skills Project. In this episode, Adam and Andreas talk about storytelling, and the impact it can have on so many of us and our career skills. If you're looking to improve your communication skills, this podcast is a must-listen.